Tradycje ludowe w muzyce wojskowych jednostek podhalańskich (1918–1939). Wybrane zagadnienia i postacie - Kozłowska, Aleksandra Anna (Zeszyty Wiejskie, 2016)
The martial music has accompanied the people since the antiquity. It has been used to announce military events or accompany marching formations but first of all to intimidate the enemy and to encourage the fighting soldiers. In November 1918 Poland restored sovereignty after 123 years of partition by the Russian Empire, the Kingdom of Prussia and the Habsburg Empire. The Polish Army was organized. In the south of Poland the highlander riflemen units were created thanks to the activity of colonel/general Andrzej Galica (1873–1945). These regiments obtained the uniforms referring to traditional folk costumes of Gorale (Polish highlanders). They wore special cloaks and hats. Also the martial music of the Polish highlander riflemen units had a source in the folk music. The folk instruments, like the bagpipes, were adapted for martial orchestras. A traditional hiking stick/weapon of the Gorale, called ciupaga, was used to conduct the orchestras. In the article three characters of highlander riflemen band masters were presented. These are: Mieczysław Mordarski (1888–1959) – the 1st highlander riflemen regiment; Maksymilian Firek (1888–1871) – the 2nd highlander riflemen regiment; Zdenko Karol Rund (1889–1962) – the 3rd highlander riflemen regiment. Nowadays Orkiestra Reprezentacyjna Straży Granicznej (The Representative Band of the Border Guard of the Republic of Poland) in Nowy Sącz and Orkiestra Garnizonowa (The Garrison Band) in Rzeszów cultivate the Polish highlanders traditions in their music.